Multimarket Contact and Mergers and Acquisitions: The Cases of Southwest Airlines and Airtran Airways in the US Airline Industry (Global Journal of Management and Business Research, 2017)
Many studies have empirically shown that multimarket contact (MMC) has collusive effects in the US airline industry. The US airline industry has recently undergone large changes. For example, some airlines have implemented mergers and acquisitions (M
Keywords: some airlines have implemented mergers and acquisitions